Plasma Concentration of Calprotectin, but Not Serum Concentration, Is a Predictive Biomarker for Clinical Remission in Ulcerative Colitis - Sailish Honap; Isabelle Aimone-Gastin; Sylvain Salignac; Justine Flayac; Justine Paoli; Laurent Peyrin-Biroulet; Abderrahim Oussalah (Inflammatory Intestinal Diseases)
Introduction: Fecal calprotectin is a validated biomarker for assessing disease activity in patients with inflammatory bowel disease (IBD). Blood calprotectin concentrations are correlated with disease activity in numerous immune-mediated inflammatory diseases. The aim of this study was to prospectively assess the diagnostic accuracy of plasma calprotectin as a potential biomarker of remission in IBD patients. Methods: This prospective observational study enrolled 131 patients at the time of infliximab administration alongside clinical assessment and blood analyses on the same day. The primary endpoint was to assess the diagnostic accuracy of plasma calprotectin for predicting remission in patients with IBD. Results: Plasma calprotectin concentration ≤10.5 ng/mL had a sensitivity of 98.6%, specificity of 100%, positive predictive value of 100%, negative predictive value of 96.3%, and an area under the receiver operating characteristic (AUROC) curve of 0.999 for diagnosing remission in patients with ulcerative colitis (UC). Plasma calprotectin had poor diagnostic accuracy for diagnosing remission in Crohn’s disease. In UC, plasma calprotectin had significantly greater diagnostic accuracy than C-reactive protein for diagnosing remission (absolute difference between AUROCs, 0.06; 95% CI: 0.008 to 0.113; p = 0.03). Plasma calprotectin concentrations were not correlated with those measured in serum samples. The median serum-to-plasma calprotectin concentration ratio was 12-fold. Conclusion: Plasma calprotectin is a promising biomarker for predicting remission in UC patients treated with infliximab.